2016
DOI: 10.1186/s12930-016-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with patient visits to the emergency department for asthma therapy in Pakistan

Abstract: BackgroundAcute asthma is a chronic condition affecting people of all ages around the world and hence, is one of the leading causes of emergency department (ED) visits and hospital admissions globally. Most of them are related to poor patient practices and a weak healthcare system. The aim of our study was to assess the reasons for the increased usage of the ED by asthmatic patients in Pakistan.MethodsA cross-sectional study was conducted on 600 asthmatic patients reporting to the ED of Civil Hospital Karachi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…According to the World Health Organization (WHO), approximately 235 million people suffered from asthma worldwide, with 157,000 requiring urgent medical aid, during 2007 (Bilal et al, 2016). The onset of asthma onset occurs before the age of 12 (years) in over half the cases.…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization (WHO), approximately 235 million people suffered from asthma worldwide, with 157,000 requiring urgent medical aid, during 2007 (Bilal et al, 2016). The onset of asthma onset occurs before the age of 12 (years) in over half the cases.…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies reported frequent visitation to ED (3 or more ED visits) among asthmatic children ranging from 26.9% to 61.6%. [ 4 5 6 7 8 9 ] In Saudi Arabia, AlJahdali et al . [ 4 ] when studied the factors associated with patients visits to the emergency department for asthma therapy found that the majority of the patients had 3 or more visits to ED accounting to 61.6% which was relatively higher compared to our study finding.…”
Section: Discussionmentioning
confidence: 99%
“…Various published papers documented that the most common reason for asthmatic children to visits ED was to obtain nebulized bronchodilator or oxygen. [ 4 5 8 ] Al-Muhsen et al . [ 5 ] reported that the majority of the patients visited ED to obtain a bronchodilator by nebulizer as well as to obtain oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma as a leading cause of hospital emergency room visits Untreated asthma and poor management of the disease can lead to frequent visits to hospital emergency rooms 8 . There are many factors that lead patients to seek care in the emergency room, including asthma severity, incorrect perceptions of the disease and its medication, lack of an asthma treatment plan, over-reliance on short acting bronchodilators, changes in weather and pollution, as well as education and socioeconomic levels.…”
Section: Introductionmentioning
confidence: 99%